Relationship between facial nerve damage and transbuccal trocar placement: an anatomical cohort study. Issue 5 (May 2016) - Lerhe, B.; Alshehri, S.; Delanoe, F.; Lauwers, F.; Lopez, R.
Abstract: The surgical treatment of ramus and mandibular angle fractures is typically performed by intraoral and transbuccal approaches. As these approaches may result in nerve damage, this anatomical study was performed to establish the relationship between the transbuccal trocar position and the likelihood of inducing facial nerve damage. Twenty dissections of the parotid regions were performed after a simulation of surgical approaches aimed at addressing mandibular condylar and angle fractures. Two trocar tubes, ramic and angular, were inserted and left in position throughout the dissection. This procedure allowed the qualitative relationship between the various tube positions and facial nerve damage to be analyzed. The potential risk of contact between the ramic trocar and the facial nerve branches was 90%, while the angular trocar was in contact in 45% of cases. There was no contact with the trunk, cervicofacial division, or temporofacial division of the facial nerve. The contacts occurred at the level of secondary division branches, particularly pronounced for superior and inferior buccal branches, despite the absence of macroscopically visible trauma. Based on these findings, it is proposed that trocars should be used in procedures aimed at addressing subcondylar or angle fractures of the mandible.